The Role of the Nurse in Humanized Birth Care - Soares, Evellyn Karoline Costa; Pereira, Natalia kelly dos Santos; Almeida, Jayran de Souza (JRG Journal of Academic Studies, 2023)
Introduction: The humanization of childbirth care, including the birth of the newborn, demands changes in behavior, attitudes and conduct from the health team that monitors the woman at this moment of utmost importance for the patient, which ensures even more respect and dignity during this process. Objectives: To analyze women's perception regarding the nursing care received during labor. Method: This is a comprehensive literature review, an integrative review that synthesizes scientific knowledge through different databases, systematized and included in the practical application of important discoveries from Google Scholar research sources; BVS, BDENF, SCIELLO. Results: After applying the inclusion and exclusion criteria, the study sample consisted of 14 articles, filtered between the years 2017 and 2023, where these studies address the role of nurses in humanized birth care. Conclusion: The nurse must provide excellent humanized care, seeking to listen to the patient, clarify all doubts, explain step by step the procedures that will be performed.